Faktor-Faktor yang Mempengaruhi Kepuasan dalam Bertransaksi Menggunakan Dompet Digital DANA pada Mahasiswa FEBI UIN Sulthan Thaha Saifuddin Jambi - Julianita Putri; Bambang Kurniawan (Lembaga Yasin AlSys, 2026)
Although the development of digital wallets has received attention in various studies, research that specifically examines the satisfaction of students of the Faculty of Islamic Economics and Business (FEBI) in using the DANA application with the variables of features, ease of use, security, and usefulness remains limited. This study aims to analyze the effects of features, ease of use, security, and usefulness on students’ satisfaction in conducting transactions using the DANA digital wallet. This study used a quantitative approach with an associative survey design. The respondents consisted of 88 students of FEBI UIN Sulthan Thaha Saifuddin Jambi from the 2021 cohort, selected through a simple random sampling technique. Data were collected using a closed-ended Likert-scale questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0. The results showed that features, ease of use, security, and usefulness had positive and significant effects on user satisfaction. The R-square value of 0.766 indicates that the four variables were able to explain 76.6% of the variation in students’ satisfaction in using the DANA digital wallet. These findings strengthen the application of the Technology Acceptance Model in the context of digital financial services. The conclusion of this study affirms that improving feature quality, ease of access, system security, and service usefulness is an important factor in increasing DANA user satisfaction. The implications of this study provide a theoretical contribution to the development of studies on digital financial technology acceptance, as well as practical implications for digital wallet service providers in improving the quality of user experience.